index de8fc5f..d0897ef 100644 (file)
@@ -46,7 +46,7 @@ Our first task will be to replace each leaf with its double:

let rec treemap (newleaf : 'a -> 'b) (t : 'a tree) : 'b tree =
match t with
-           | Leaf x -> Leaf (newleaf x)
+           | Leaf i -> Leaf (newleaf i)
| Node (l, r) -> Node (treemap newleaf l,
treemap newleaf r);;

@@ -76,7 +76,7 @@ decide to do something else to the leaves without needing to rewrite
`treemap`.  For instance, we can easily square each leaf instead by
supplying the appropriate `int -> int` operation in place of `double`:

-       let square x = x * x;;
+       let square i = i * i;;
treemap square t1;;
- : int tree =ppp
Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
tree that is ready to accept any `int -> int` function and produce the
updated tree.

+\tree (. (. (f 2) (f 3)) (. (f 5) (. (f 7) (f 11))))

\f      .
_____|____
@@ -107,7 +108,7 @@ updated tree.
That is, we want to transform the ordinary tree `t1` (of type `int
tree`) into a reader object of type `(int -> int) -> int tree`: something
that, when you apply it to an `int -> int` function `f` returns an `int
-tree` in which each leaf `x` has been replaced with `f x`.
+tree` in which each leaf `i` has been replaced with `f i`.

With previous readers, we always knew which kind of environment to
expect: either an assignment function (the original calculator
@@ -132,7 +133,7 @@ function of type `int -> int` to.

let rec treemonadizer (f : 'a -> 'b reader) (t : 'a tree) : 'b tree reader =
match t with
-           | Leaf x -> reader_bind (f x) (fun x' -> reader_unit (Leaf x'))
+           | Leaf i -> reader_bind (f i) (fun i' -> reader_unit (Leaf i'))
| Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
@@ -164,8 +165,8 @@ For instance, we can use a state monad to count the number of nodes in
the tree.

type 'a state = int -> 'a * int;;
-       let state_unit a = fun i -> (a, i);;
-       let state_bind u f = fun i -> let (a, i') = u i in f a (i' + 1);;
+       let state_unit a = fun s -> (a, s);;
+       let state_bind_and_count u f = fun s -> let (a, s') = u s in f a (s' + 1);;

Gratifyingly, we can use the `treemonadizer` function without any
modification whatsoever, except for replacing the (parametric) type
@@ -173,9 +174,9 @@ modification whatsoever, except for replacing the (parametric) type

let rec treemonadizer (f : 'a -> 'b state) (t : 'a tree) : 'b tree state =
match t with
-           | Leaf x -> state_bind (f x) (fun x' -> state_unit (Leaf x'))
-           | Node (l, r) -> state_bind (treemonadizer f l) (fun x ->
-                              state_bind (treemonadizer f r) (fun y ->
+           | Leaf i -> state_bind_and_count (f i) (fun i' -> state_unit (Leaf i'))
+           | Node (l, r) -> state_bind_and_count (treemonadizer f l) (fun x ->
+                              state_bind_and_count (treemonadizer f r) (fun y ->
state_unit (Node (x, y))));;

Then we can count the number of nodes in the tree:
@@ -210,7 +211,7 @@ But I assume Chris means here, adjust the code so that no corrections of this so
One more revealing example before getting down to business: replacing
`state` everywhere in `treemonadizer` with `list` gives us

-       # treemonadizer (fun x -> [ [x; square x] ]) t1;;
+       # treemonadizer (fun i -> [ [i; square i] ]) t1;;
- : int list tree list =
[Node
(Node (Leaf [2; 4], Leaf [3; 9]),
@@ -220,16 +221,21 @@ Unlike the previous cases, instead of turning a tree into a function
from some input to a result, this transformer replaces each `int` with
a list of `int`'s.

+<!--
+We don't make it clear why the fun has to be int -> int list list, instead of int -> int list
+-->
+
+
Now for the main point.  What if we wanted to convert a tree to a list
of leaves?

type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
-       let continuation_unit x c = c x;;
-       let continuation_bind u f c = u (fun a -> f a c);;
+       let continuation_unit a = fun k -> k a;;
+       let continuation_bind u f = fun k -> u (fun a -> f a k);;

let rec treemonadizer (f : 'a -> ('b, 'r) continuation) (t : 'a tree) : ('b tree, 'r) continuation =
match t with
-           | Leaf x -> continuation_bind (f x) (fun x' -> continuation_unit (Leaf x'))
+           | Leaf i -> continuation_bind (f i) (fun i' -> continuation_unit (Leaf i'))
| Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
continuation_bind (treemonadizer f r) (fun y ->
continuation_unit (Node (x, y))));;
@@ -238,7 +244,7 @@ We use the continuation monad described above, and insert the
`continuation` type in the appropriate place in the `treemonadizer` code.
We then compute:

-       # treemonadizer (fun a c -> a :: (c a)) t1 (fun t -> []);;
+       # treemonadizer (fun a k -> a :: (k a)) t1 (fun t -> []);;
- : int list = [2; 3; 5; 7; 11]

We have found a way of collapsing a tree into a list of its leaves.
@@ -249,7 +255,7 @@ note that an interestingly uninteresting thing happens if we use the
continuation unit as our first argument to `treemonadizer`, and then
apply the result to the identity function:

-       # treemonadizer continuation_unit t1 (fun x -> x);;
+       # treemonadizer continuation_unit t1 (fun i -> i);;
- : int tree =
Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))

@@ -257,25 +263,25 @@ That is, nothing happens.  But we can begin to substitute more
interesting functions for the first argument of `treemonadizer`:

(* Simulating the tree reader: distributing a operation over the leaves *)
-       # treemonadizer (fun a c -> c (square a)) t1 (fun x -> x);;
+       # treemonadizer (fun a k -> k (square a)) t1 (fun i -> i);;
- : int tree =
Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))

(* Simulating the int list tree list *)
-       # treemonadizer (fun a c -> c [a; square a]) t1 (fun x -> x);;
+       # treemonadizer (fun a k -> k [a; square a]) t1 (fun i -> i);;
- : int list tree =
Node
(Node (Leaf [2; 4], Leaf [3; 9]),
Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))

(* Counting leaves *)
-       # treemonadizer (fun a c -> 1 + c a) t1 (fun x -> 0);;
+       # treemonadizer (fun a k -> 1 + k a) t1 (fun i -> 0);;
- : int = 5

We could simulate the tree state example too, but it would require
generalizing the type of the continuation monad to

-       type ('a -> 'b -> 'c) continuation = ('a -> 'b) -> 'c;;
+       type ('a, 'b, 'c) continuation = ('a -> 'b) -> 'c;;

---------------------
@@ -284,37 +290,37 @@ Of course, by now you may have realized that we have discovered a new

type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
-       let tree_unit (x: 'a) = Leaf x;;
+       let tree_unit (a: 'a) = Leaf a;;
let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
match u with
-           | Leaf x -> f x
+           | Leaf a -> f a
| Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;

For once, let's check the Monad laws.  The left identity law is easy:

-    Left identity: bind (unit a) f = bind (Leaf a) f = fa
+    Left identity: bind (unit a) f = bind (Leaf a) f = f a

To check the other two laws, we need to make the following
observation: it is easy to prove based on `tree_bind` by a simple
induction on the structure of the first argument that the tree
resulting from `bind u f` is a tree with the same strucure as `u`,
-except that each leaf `a` has been replaced with `fa`:
+except that each leaf `a` has been replaced with `f a`:

-\tree (. (fa1) (. (. (. (fa2)(fa3)) (fa4)) (fa5)))
+\tree (. (f a1) (. (. (. (f a2) (f a3)) (f a4)) (f a5)))

.                         .
__|__                     __|__
|   |                     |   |
-                     a1  .                    fa1  .
+                     a1  .                   a1  .
_|__                     __|__
|  |                     |   |
-                        .  a5                    .  fa5
+                        .  a5                    .  f a5
bind         _|__       f   =        __|__
|  |                    |   |
-                       .  a4                   .  fa4
+                       .  a4                   .  f a4
__|__                   __|___
|   |                   |    |
-                     a2  a3                 fa2  fa3
+                     a2  a3                f a2  f a3

Given this equivalence, the right identity law

@@ -331,26 +337,26 @@ As for the associative law,
we'll give an example that will show how an inductive proof would
proceed.  Let `f a = Node (Leaf a, Leaf a)`.  Then

-\tree (. (. (. (. (a1)(a2)))))
-\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))  ))
+\tree (. (. (. (. (a1) (a2)))))
+\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))))

.
____|____
.               .            |       |
bind    __|__   f  =    __|_    =      .       .
|   |           |   |        __|__   __|__
-               a1  a2         fa1 fa2       |   |   |   |
+               a1  a2        f a1 f a2      |   |   |   |
a1  a1  a1  a1

Now when we bind this tree to `g`, we get

-                  .
-              ____|____
-              |       |
-              .       .
-            __|__   __|__
-            |   |   |   |
-           ga1 ga1 ga1 ga1
+                   .
+              _____|______
+              |          |
+              .          .
+            __|__      __|__
+            |   |      |   |
+          g a1 g a1  g a1 g a1

At this point, it should be easy to convince yourself that
using the recipe on the right hand side of the associative law will